The Impact of Financial Technology, Self-Control, And Financial Knowledge on the Financial Management Behavior of Management Students at the Faculty of Economics and Business, Universitas Swadaya Gunung Jati Cirebon, in the Digital Era - Dewi Purwasih; Maiyaliza (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to analyse the impact of Financial Technology (Fintech), Self-Control, and Financial Knowledge on Financial Management Behaviour among students in the Faculty of Economics and Business (FEB) Management at Swadaya Gunung Jati University (UGJ) in Cirebon in the digital age. Integrating the Technology Acceptance Model (TAM) and the Theory of Planned Behaviour (TPB), this study explores how access to technology, psychological self-control, and financial literacy shape personal financial management behaviour. The research method employed was an associative quantitative approach with a sample of 387 respondents selected using stratified proportionate random sampling. Data were collected via an online questionnaire and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results indicate that, individually, Self-Control and Financial Knowledge have a positive and significant influence on Financial Management Behaviour, with financial knowledge being the most dominant factor. Conversely, Financial Technology was found to have no significant partial influence on students’ financial management behaviour. However, simultaneously, these three independent variables had a significant influence on Financial Management Behaviour with a coefficient of determination (R²) of 53.9%, which is categorised as a moderate level of influence. These findings indicate that although access to technology.